KEMAMPUAN MENULIS TEKS NARASI MELALUI PROJECT BASED LEARNING BERBANTUAN STORY MAP PADA SISWA SEKOLAH DASAR - Fitra Ramdani Ointu; Lamsike Papeda; Sitti Rahmawati Talango (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to describe the process of implementing the Project Based Learning (PjBL) model in learning to write narrative texts and analyze the responses and involvement of fourth-grade students of SDN 21 Limboto during the process. This type of research is classroom action research. The subjects in this study were 26 fourth-grade students of SDN 7 Limboto, 10 boys and 16 girls. The data analysis techniques used in this study are quantitative and qualitative. Based on the results of classroom action research that has been carried out in two cycles in fourth-grade students of SDN 21 Limboto, it can be concluded that the implementation of the Project-Based Learning (PjBL) model has been proven to improve the ability to write narrative texts of fourth-grade students of SDN 21 Limboto. This increase can be seen from the results of the narrative writing test which shows an increase in the average score and percentage of learning completion from the pre-cycle to Cycle I, then increased again in Cycle II. Students become more able to develop story ideas, arrange plots coherently, use narrative elements appropriately, and improve the use of spelling and punctuation in writing. Thus, students' narrative writing skills experienced a significant increase after implementing the Project-Based Learning (PjBL) model.